2006
DOI: 10.1016/j.acn.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Improving the ecological validity of executive functioning assessment

Abstract: The current study investigated ways to improve the ecological validity of the neuropsychological assessment of executive functioning through the formal assessment of compensatory strategies and environmental cognitive demands. Results indicated that the group of executive functioning tests (i.e., Trail Making Test, Wisconsin Card Sorting Test, Stroop, and Controlled Oral Word Association Test) accounted for 18-20% of the variance in everyday executive ability as measured by the Dysexecutive Questionnaire and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
249
2
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(273 citation statements)
references
References 26 publications
11
249
2
11
Order By: Relevance
“…Ecological validity of neuropsychological assessment remains an ever present concern (Chaytor et al, 2006;Moritz et al, 2004;Odhuba et al, 2005;Wood & Liossi, 2006). As an example, the antemortem clinical neuropsychological testing in the concussed patient previously described who met PPCS criteria and who at autopsy had verified pathology of brain injury, was all normal yet this individual had "real-world" difficulty running his business, problems not evident before his injury (Bigler, 2004).…”
Section: Ecological Validity Of the Clinical Neuropsychological Approachmentioning
confidence: 99%
“…Ecological validity of neuropsychological assessment remains an ever present concern (Chaytor et al, 2006;Moritz et al, 2004;Odhuba et al, 2005;Wood & Liossi, 2006). As an example, the antemortem clinical neuropsychological testing in the concussed patient previously described who met PPCS criteria and who at autopsy had verified pathology of brain injury, was all normal yet this individual had "real-world" difficulty running his business, problems not evident before his injury (Bigler, 2004).…”
Section: Ecological Validity Of the Clinical Neuropsychological Approachmentioning
confidence: 99%
“…Examples of tests used to examine executive processes include dual-task performance, Stroop, Wisconsin Card Sorting, Tower of London, delayed alternation, and assorted working memory (WM) tasks. Such paradigms have proved a reliable method for demonstrating executive control deficits across a range of clinical conditions (Dalrymple-Alford et al 1994;Diamond 1996;Baddeley et al 1997;Barkley 1997;Diamond et al 1997;Konrad et al 2000;Baddeley et al 2001;Bennetto et al 2001;Gilotty et al 2002;Sharma and Antonova 2003;Simon et al 2003), with recent work also indicating a strong relationship between executive control deficits on laboratory tasks and real-world behavioral problems (Burgess et al 1998;Kibby et al 1998;Moriyama et al 2002;Kalechstein et al 2003a;Odhuba et al 2005;Chaytor et al 2006). …”
Section: Executive Control Processes and Their Constituent Neural Netmentioning
confidence: 99%
“…They base their skepticism on a study by Chaytor et al (2006) in which the correlation of the DEX with executive tests was not particularly high.…”
Section: To the Editorsmentioning
confidence: 99%
“…In reference, we would like to highlight that the study by Chaytor et al (2006) is grounded on the data of a group of merely 46 patients, with a variety of neurological disorders, where correlation was carried out with a few tests measuring executive performance and experimental methods (Wisconsin Card Sorting Test (WCST), Trail Making Test, Stroop Color and Word Test, Controlled Oral Word Association Test (COWAT)), and between the DEX and other questionnaires. This study found a moderate correlation between the DEX and the Stroop task (r ¼0.35) and weak or no correlation between the DEX and the Trail Making Test-Part B, COWAT and WCST (r ¼ 0.25, r ¼0.28, r ¼0.03, respectively).…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation